Involvement of the Nrf2-Keap1 signaling pathway in protection against thallium-induced oxidative stress and mitochondrial dysfunction in primary hippocampal neurons. (1st February 2020) - Lin, Guodong; Sun, Yawei; Long, Jianhai; Sui, Xin; Yang, Jun; Wang, Qian; Wang, Shuai; He, Huanhuan; Luo, Yuan; Qiu, Zewu; Wang, Yongan
Highlights: The Nrf2-Keap1 pathway is a potential therapeutic target against thallium poisoning. Nrf2-Keap1 pathway protects against thallium-induced oxidative stress and mitochondrial dysfunction. t-BHQ protects hippocampal neurons against thallium poisoning through activating the Nrf2 pathway. Abstract: Thallium ion (Tl + ) and its neurotoxic products are widely known to cause severe neurological complications. However, the exact mechanism of action remains unknown, with limited therapeutic options available. This study aims to examine the toxic effects of Thallium (I) Nitrate (TlNO3 ) on primary hippocampal neurons of E17-E18 Wistar rat embryos, and the potential neuroprotective role of Nrf2- Keap1 signaling pathway against thallium-induced oxidative stress and mitochondrial dysfunction. TlNO3 induces a significant increase in reactive oxygen species levels and mitochondrial dysfunction in primary hippocampal neurons. Furthermore, the Nrf2-Keap1 signaling pathway played a protective role against TlNO3 -induced hippocampal neuronal cytotoxicity. Moreover, mitochondrial fusion protein Mitofusin 2 (Mfn2) levels significantly decreased in hippocampal neurons when exposed to TlNO3, indicating that Mfn2 protein levels are linked to TlNO3 -induced neurotoxicity. t-BHQ, a Nrf2 and phase II detoxification enzyme inducer, counteracted the oxidative damage in hippocampal neurons by activating the Nrf2-Keap1 signaling pathway after TlNO3 exposure; the activated Nrf2-Keap1 pathway could then maintain Mfn2 function by regulating Mfn2 protein expression. Thus, Nrf2-Keap1 pathway activation plays a protective role in Tl + -induced brain damage, and specific agonists have been identified to have great potential for treating thallium poisoning.